WATERFRONT DEVELOPMENT IN MALAYSIA - Azlina Md. Yassin (Penerbit UTHM, 2014)
The purpose of the book was to examine waterfront development in Malaysia, identifying the main constraints currently existing and to identify significant attributes for successful waterfront development from international. This book will be organised into seven chapters. Chapter 1 presented an overview of waterfront development theory, included a definition of waterfronts and waterfront development, significant of waterfront zone and an evolution of waterfront development throughout the world. Chapter 2 focused on successful experiences from other developed countries and guidelines and principles for successful waterfront development. The next two chapters reviewed the waterfront development practices from international as well as waterfront development practiced in malaysia. The next two chapters focused with a discussion on the topic being studied and then concludes with a conclusion and recommendation for enhancing waterfront development in Malaysia.